Short communicationsCoronary artery perforation during diagnostic coronary angiography resulting in acute pericarditis - Duyuler, Serkan; Bayır, Pınar Türker; Korkmaz, Ahmet; Güray, Ümit; Kısacık, Halil Lütfi (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report a case of coronary artery perforation during diagnostic coronary angiography. No cardiac biomarker elevation was observed. However, the patient suffered acute pericarditis which was treated conservatively.